Second harmonic imaging of chloroplasts using the two-photon laser scanning microscope - Reshak, Ali Hussain; Sarafis, Vassilios; Heintzmann, Rainer (Micron (Oxford, England, 2009)
BACKGROUND: Second harmonic information reveals information about the structure of spatially oriented structures with an asymmetry. We study the second harmonic images of the grana and intergranal parts of chloroplasts in the leaves of the shade moss Plagiomnium affine. RESULTS: A two-photon microscope with blocking filters to suppress fluorescence generated both forward and backward second harmonic illumination to be captured. In the starch free chloroplasts of the single cell layered laminae strong second harmonic generation (SHG) from the granal regions was emitted. Upon illumination the chloroplasts changed their orientation affecting the SHG signal. Chloroplast is reoriented upon illumination. CONCLUSIONS: SHG signals were successfully obtained from the grana without any possible confusion from SHG starch grains due to their absence.
Keywords: škrob; Photons; fotony; Fluorescence; Time Factors; Birefringence; Lighting; Thylakoids; Microscopy, Confocal; Starch; fluorescence; konfokální mikroskopie; osvětlení; Bryopsida; mechy; dvojitý lom; časové faktory; Microscopy, Fluorescence, Multiphoton; tylakoidy; mikroskopie fluorescenční multifotonová